Faktor-Faktor yang Berhubungan dengan Perilaku PSN pada Masyarakat di Desa Balekambang Kabupaten Bogor: Studi Cross-Sectional - Ismie Rahma Alya; Cicilia Nony Ayuningsih Bratajaya; Mila Sartika; Hana Priscilla Frudence Sohilait (Universitas Nurul Jadid, 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a major tropical health problem in Indonesia, including West Java, which experiences an increase in cases during the transitional season. Efforts to eradicate mosquito breeding sites through Mosquito Breeding Site Eradication (PSN/3M Plus) programs as a preventive measure against DHF have not been optimally implemented in Balekambang Village, West Java. Objective: This study aimed to determine the determinants of mosquito nest eradication behavior among the community in Balekambang Village. Methods: This study employed a quantitative method with a descriptive correlational design and a cross-sectional approach. This design identifies associations but cannot establish causality. The study population consisted of residents of Balekambang Village, with a sample of 85 respondents selected using purposive sampling techniques. Data were collected using questionnaires on knowledge, attitudes, and mosquito nest eradication behavior, then analyzed using the Chi-Square test. Results: The bivariate analysis showed no significant relationship between age (p-value = 0.546) and gender (p-value = 0.659) with mosquito nest eradication behavior. However, there were significant relationships between education level (p-value = 0.001), level of knowledge (p-value = 0.018), and attitudes (p-value = 0.001) with community mosquito nest eradication behavior. Conclusion: This study concluded that education, knowledge, and attitudes were significantly associated with mosquito breeding site eradication behavior in the community. Therefore, healthcare workers are expected to provide routine education and information related to mosquito nest eradication in order to increase community awareness and participation in DHF prevention.